2019
DOI: 10.1002/eat.23012
|View full text |Cite
|
Sign up to set email alerts
|

Preserved white matter microstructure in adolescent patients with atypical anorexia nervosa

Abstract: Objective Patients with atypical anorexia nervosa (AN) are often in the normal‐weight range at presentation; however, signs of starvation and medical instability are not rare. White matter (WM) microstructural correlates of atypical AN have not yet been investigated, leaving an important gap in our knowledge regarding the neural pathogenesis of this disorder. Method We investigated WM microstructural integrity in 25 drug‐naïve adolescent patients with atypical AN and 25 healthy controls, using diffusion tensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Small‐scale studies of brain structure and function have pointed to potential pathogenetic differences between AN and AAN. For example, in contrast to AN, alterations in gray and white matter microstructure do not appear to be common features of AAN; however, this may reflect less severe undernutrition in AAN (Olivo et al, 2018; Olivo et al, 2019). Moreover, food‐related neural responses in AAN may differ from what is typically seen in AN (Olivo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Small‐scale studies of brain structure and function have pointed to potential pathogenetic differences between AN and AAN. For example, in contrast to AN, alterations in gray and white matter microstructure do not appear to be common features of AAN; however, this may reflect less severe undernutrition in AAN (Olivo et al, 2018; Olivo et al, 2019). Moreover, food‐related neural responses in AAN may differ from what is typically seen in AN (Olivo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies report lower FA in widespread WM regions, including the corpus callosum (CC) (Frieling et al, 2012;Frank et al, 2013;Shott et al, 2016;Gaudio et al, 2017;Phillipou et al, 2018;von Schwanenflug et al, 2019), fornix fibers (Kazlouski et al, 2011;Frank et al, 2013;Gaudio et al, 2017), thalamus (Frieling et al, 2012;Hu et al, 2017), cingulum (Kazlouski et al, 2011;Frank et al, 2013), posterior thalamic radiation (PTR) (Phillipou et al, 2018), superior longitudinal fasciculus (SLF) (Via et al, 2014), fronto-occipital fasciculus (FOF) (Kazlouski et al, 2011;Via et al, 2014), corona radiation (Shott et al, 2016;Phillipou et al, 2018) and cerebellum (Nagahara et al, 2014;Shott et al, 2016). Five studies, however, observed no significant FA differences between AN patients and HC (Yau et al, 2013;Cha et al, 2016;Pfuhl et al, 2016;Bang et al, 2018;Olivo and Swenne, 2019). Two studies also reported higher FA in corona radiation, SLF, FOF, PTR, and CC (Frank et al, 2013;Vogel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Further, methodological differences between tract-based spatial statistics (TBSS) and voxel-based analysis (VBA) could account for heterogeneity in WM findings, as TBSS seems to be more sensitive to FA reductions (29). Concerning body mass index (BMI) differences, an interesting study of Olivo et al (30) compared 25 adolescents with atypical AN with 25 HC, who did not differ with respect to BMI. They did not find WM differences and discussed weight-related WM abnormalities as most likely in other studies.…”
Section: Introductionmentioning
confidence: 99%